Prevalence and risk factors of exposure keratopathy among critically ill patients: A systematic review and meta‐analysis - Yulu Chen; Jing He; Qiuping Wu; Shi Pu; Caiping Song (Wiley, 2024)
Abstract Aims To identify the incidence, prevalence and risk factors of exposure keratopathy (EK) among critically ill patients. Design Systematic review and meta‐analysis, in accordance with the PRISMA 2020 Statement. Methods The Cochrane Library, PubMed, Embase, Web of Science, Cumulative Index to Nursing and Allied Health Literature (CINAHL), China Knowledge Resource Integrated Database (CNKI), Chinese Biomedical Database (CBM), Weipu Database (VIP) and WanFang Database were systematically searched from inception to June 2022. Observational studies that reported EK among paediatric and adult critically ill patients were screened and included original articles based on the inclusion criteria. Two reviewers independently completed data extraction and quality assessments. Subgroup analysis investigated potential causes of heterogeneity. Results Of the 4508 studies identified, 23 studies involving 3519 subjects were included. The pooled prevalence of EK was 34.0%, and the pooled incidence rate of EK was 23.0%. Risk factors associated with EK in critically ill patients included lagophthalmos, chemosis, eye blinks <5 times per minute, mechanical ventilation, sedation, lower Glasgow Coma Scale (GCS) score and higher Acute Physiology and Chronic Health Evaluation (APACHE) II score. Conclusion This review shows that EK rates are high in critically ill patients and are influenced by multiple factors. Medical staff should pay more attention to EK in critically ill patients, conduct professional evaluations and implement targeted eye care protocols to reduce its occurrence. Implications for Practice This study shows the frequency of and multiple risk factors for EK in critically ill patients, which provides evidence‐based guidance for nurses to evaluate the risk of EK in critically ill patients and take appropriate precautions to reduce the risk. Protocol Registration The protocol was registered in PROSPERO (https://www.crd.york.ac.uk/prospero/) (CRD42022346964). Patient or Public Contribution No patient or public contribution.